Executive Committee Minutes 2014-10-30 - Academic Senate:::::::::
Agenda – Approved. Minutes of 10/16 – Approved. Chair Report. Provost Report. Statewide Senator Report. Vice Chair Report. Question for Vice President of Administration and Finance. EPC Report. FSAC Report. University Studies Curriculum Committee proposal discussed. Revision to the Lecturers in Departmental Governance policy – approved for Senate agenda. CFA Report. Associated Students Report. Honorary Degree Committee membership. Graduation Initiative presentation at the Senate approved for Senate agenda. 2015 Faculty Retreat discussion. Senate agenda approved.